2016
DOI: 10.1080/10253890.2016.1203413
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent role of vesicular glutamate transporter 3 in stress-regulation and related anxiety phenotype during the early postnatal period

Abstract: Stress and related disorders are in the focus of interest and glutamate is one of the most important neurotransmitters that can affect these processes. Glutamatergic neurons are characterized by vesicular glutamate transporters (VGluT1-3) among which vGluT3 is unique contributing to the non-canonical, neuromodulatory effect of glutamate. We aimed to study the role of vGluT3 in stress axis regulation and related anxiety during the early postnatal period using knockout (KO) mice with special focus on sex differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Moreover, the reduced stress reactivity to an immune challenge in AX mice pups is also a reflection of a disrupted coping style. Previously LPS was able to induce significant stimulation in ACTH and corticosterone levels in adult (Lolait et al 2007) and postnatal (Balázsfi et al 2016) mice, which was replicated in our present experiments. Although HAB rats previously demonstrated a larger increase in corticosterone levels to LPS administration than LAB rats (Salome et al 2008), their stress reaction to social defeat was also diminished (Frank et al 2006), similarly to our results.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, the reduced stress reactivity to an immune challenge in AX mice pups is also a reflection of a disrupted coping style. Previously LPS was able to induce significant stimulation in ACTH and corticosterone levels in adult (Lolait et al 2007) and postnatal (Balázsfi et al 2016) mice, which was replicated in our present experiments. Although HAB rats previously demonstrated a larger increase in corticosterone levels to LPS administration than LAB rats (Salome et al 2008), their stress reaction to social defeat was also diminished (Frank et al 2006), similarly to our results.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies clearly suggested an enhanced maternal separation-induced USV emission as a sign of exaggerated anxiety both in rat and mice pups (Winslow, Insel 1991;Iijima, Chaki 2005;Varga et al 2015;Balázsfi et al 2016). Moreover, rats showing higher USV at PND 10 during a 2 min test were more anxious in their adulthood as measured in open field (Brunelli, Hofer 2007).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thus, these studies are reviewed here in somewhat greater detail. No significant links between immune function and USV were found in the two publications that we could trace dealing with early postnatal immune stimulation . The few reports available on ultrasonic calling and stimulation of the immune system during experimentally induced inflammatory or autoimmune processes are mentioned below.…”
Section: Immune Activation and Vocalizationmentioning
confidence: 88%
“…Interestingly, similar anxiety-like behaviors were noted in mice lacking VGLUT3 signaling. Deletion of VGLUT3 enhanced innate fear in newborn mice, while adult VGLUT3 -/mice elicited marked neophobia toward anxiogenic contexts (Amilhon et al, 2010;Balázsfi et al, 2016).…”
Section: Vglut3-mglur5 Axis In Striatal Networkmentioning
confidence: 96%